Covid-19 Associated with Stigma among Nurses in the Frontline: A Phenomenological Study - De los Santos, Janet Alexis; Arradaza, Van Jason; Galvez, Jhucyl Mae (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: There is a scarcity of literature presenting the lived experience of nurses working in hospital and community settings in the Philippines during the COVID-19 pandemic. Objective: This paper aims to describe the lived experiences of COVID-19-related stigma among these nurses on the frontline. Methods: This study utilized a qualitative design using a transcendental phenomenological approach. Fourteen frontline nurses participated in the interview conducted during the first quarter of 2020. Results: Four overarching themes were unearthed from the participants' narratives, namely: (1) Social Stigma and Discrimination, (2) Self-Stigma, (3) Effects of COVID 19 stigma with the subtheme of (3.1) anxiety, (3.2) loneliness, and (3.3) fear, and (4) Resilience from experience. Conclusion: The study's findings provide insight into the situational experiences and the deleterious effects of stigma on nurses working on the frontline. Recommendation: Health institutions should provide a lens on these needs and implement supportive interventions to uplift the spirits of these nurses working on the frontline.